The computational study of external heat flux and silicon doping effect on displacement of C20 molecule in a carbon nanotube (CNT): A molecular dynamics method - Xinwei Guo; S. Mohammad Sajadi; Nafis Ahmad; Tariq J. Al-Musawi; Navid Nasajpour-Esfahani; Sh. Esmaeili; M. Abdulfadhil Gatea; Ali Alsalamy; D. Toghraie (Results in Physics, 2023)
This study focuses on the behavior of the Carbon Nanotube (CNT)-C20 system as a nano-pumping configuration for drug delivery processes. The system was modeled using a molecular dynamics (MD) method, and the effects of external heat flux and silicon doping were investigated. The predicted MD outputs showed high stability throughout the nanopumping process, even when different ratios of external heat flux were applied. The entropy value of the CNT-C20 system decreases from 412.91 to 403.394 eV/K as the heat flux increases to 0.03 W/m2. Also, the kinetic energy of the target atomic sample increased from 3.50 to 5.42 eV as heat flux increased. This kinetic energy enlarging occurred for the translational component of the target molecule’s kinetic energy, and the rotational component didn’t change effectively. Additionally, the results show that increasing atomic doping of silicon particles from 1 to 3 % decreased the displacement time of C20 molecule (7.22 ps for a 3 % doping ratio), indicating that atomic doping may also improve the nano-pumping process. By increasing Si doping to 3 %, the potential energy decreased, and the stability of the defined compound was reduced. This procedure caused the target molecule to not stabilize inside the nanotube sample, and this molecule displaced inside the deliverer system in less time. However, the negative ratio of potential energy showed physical stability of the total system wasn’t disrupted. With further doping increase to 5 %, the defined compound’s potential energy increased and stability enlarged. This process can be delayed nano-pumping procedure. Overall, the outcomes of this simulation provide insights into the optimal method for pumping fluids at the nanoscale and for drug delivery systems. These findings have practical implications for developing more efficient and effective drug delivery technologies that can help improve patient outcomes.